Aseptic meningitis, hepatitis and cholestasis induced by trimethoprim/sulfamethoxazole: a case report - J. A. A. van Asperdt; R. A. De Moor (BMC, 2021)
Abstract Background Drug-induced aseptic meningitis is a rare, but challenging diagnosis, most commonly reported with nonsteoroidal anti-inflammatory drugs (NSAIDs) and antibiotics. Trimethoprim/sulfamethoxazole (TMP/SMX) is a sulfonamide that is widely used in clinical practice for the treatment and prophylaxis of various infections. The most common side effects associated with TMP/SMX are generally mild and self-limited, but serious side effects have been reported, including liver injury and aseptic meningitis. Case presentation We report a 2,5 year old Dutch girl with both drug-induced aseptic meningitis and drug-induced liver injury while using TMP/SMX prophylaxis. Ursodeoxycholic acid was started because of cholestatic injury. After cessation of TMP/SMX, full convalescence was reached within weeks. Conclusions This is the first report of a young patient with both aseptic meningitis and drug-induced liver injury caused by TMP/SMX. Drug-induced aseptic meningitis and cholestatic hepatitis constitute a considerable diagnostic challenge to clinicians. In addition to a thorough evaluation for infectious causes, clinicians should be aware of drug-induced aseptic meningitis and cholestatic hepatitis.